Direct Dynamic Evidence of Charge Separation in a Dye‐Sensitized Solar Cell Obtained under Operando Conditions by Raman Spectroscopy. (9th April 2020) - Mao, Zhu; Ye, Yutong; Lv, Haiming; Han, Xiao Xia; Park, Yeonju; Zang, Libin; Zhao, Bing; Jung, Young Mee
Abstract: Interfaces play an important role in enhancing the energy conversion performance of dye‐sensitized solar cells (DSCs). The interface effects have been studied by many techniques, but most of the studies only focused on one part of a DSC, rather than on a complete solar cell. Hence, monitoring the interface evolution of a DSC is still very challenging. Here, in situ/operando resonance Raman (RR) spectroscopic analyses were carried out to monitor the dynamics of the photovoltaic conversion processes in a DSC. We observed the creation of new species (i.e., polyiodide and iodine aggregates) in the photosensitization process. We also obtained molecular‐scale dynamic evidence that the bands from the C=C and C=N bonds of 2, 2′‐bipyridyl (bpy), the S=C=N bonds of the NCS ligand, and photochemical products undergo reasonably strong intensity and frequency changes, which clearly demonstrates that they are involved in charge separation. Furthermore, RR spectroscopy can also be used to quickly evaluate the performance of DSCs. Abstract : In situ resonance Raman spectroscopy was used for noninvasive and nondestructive microscopic investigations of dynamic interface evolutions in dye‐sensitized solar cells under operando conditions. The creation of new species was observed, and interactions between charge separation pathways and molecular vibrations were studied, providing new insight for the optimization of dye‐sensitized solar cells.